Analisis Strategi Pemasaran Perusahaan Dagang Dalam Meningkatkan Penjualan - Nursalamah; Arsidin Batubara; Fakhrurrozi; Imelda Marthauli Pardede; Edison Siregar (Yayasan Perguruan Kampus, 2025)
In this era of globalization, economic development has progressed in the activities of companies operating in the marketing sector, especially trade. Trading companies are required to implement effective marketing strategies to increase sales and maintain their existence. Marketing strategy is an important thing in a company, because marketing strategy is the main key in determining the appropriate steps to meet sales targets and competitive advantages. This study aims to analyze marketing strategies that can be used by trading companies to increase sales. The method used in this study is to use a qualitative approach. The data sources used are secondary data, which are data collected indirectly, not from original sources, but data from magazines or journals, and data from the internet. Based on the results of the analysis, it shows that effective marketing strategies implemented by a company are market segmentation, targeting, positioning, marketing mix, SWOT analysis, and digital marketing. By implementing these strategies, the company can increase sales and build competitive advantages.